ZHU DANDAN (B): LEADERSHIP DEVELOPMENT - Ma, S.; Zhou, Y.; Trigo, V. (Business Case, 2020)
In March 2016, the associate finance director at Bevaco China (Bevaco), an American multinational firm in China, faced a tough decision. Over the past four years, she had worked diligently to shift her focus from managing work to leading people. She was assigned to work in a joint venture between Bevaco and Mask, a leading Chinese private enterprise, where she faced numerous challenges. A year later, she moved back to Bevaco and worked with a charismatic and visionary leader, who inspired her to further develop her leadership as she built a 50-member team. However, as the associate finance director was enjoying her progress in leadership development, the leader resigned and the team’s work was to be outsourced. Amid this upheaval, she received an offer to work in a globalizing high-tech Chinese firm with the opportunity to work overseas. Was she ready for this opportunity? Could she overcome the challenge of a new company and lead others in a global context? Learning Objective: This case is suitable for graduate- and executive-level courses on leadership development; leadership styles; differences in management approaches and organizational cultures between foreign-invested firms and Chinese private enterprises; or the motivations of the post-1980s generation in China now at its working prime. After working through the case and assignment questions, students will be able to do the following: Distinguish the difference between management and leadership. Discuss ways to develop the leadership of high potential employees. Understand the challenges faced by the post-1980s generation in leadership development. Analyze different leadership styles and employee responses under different leadership styles. Appreciate ethics and morals in leadership. Evaluate different management approaches and cultures in different firms. Issues:leadership development, leadership style, leadership and ethics, Chinese business culture Disciplines: Organisational Behaviour/Leadership, International Industries: Manufacturing Setting: China, Large, 2016 Intended Audience: MBA/Postgraduate